Low voltage varistor ceramics based on SnO2 - Dhage, S. R.; Ravi, V.; Yang, O. B. (Bulletin of Materials Science, 2007)
The nonlinear current (I)-voltage (V) characteristics of tin dioxide doped with either Nb2O5 and CoO or Sb2O3 and CoO show promising values of nonlinear coefficient (alpha) values (similar to 11) with low breakdown voltages (E-B, similar to 40 V mm(-1)). The pentavalent antimony or niobium acts as donor and increases the electronic conductivity. The crucial parameter for obtaining low breakdown voltage is the grain size, which depends upon sintering duration and temperature of these oxide ceramics.
Keywords: Chemical synthesis; electronic materials; Microstructure; tin oxide; X-ray diffraction

Varistor property of SnO2 center dot CoO center dot Ta2O5 ceramic modified by barium and strontium - Dhage, S. R.; Ravi, V.; Yang, O. B. (Journal of Alloys and Compounds, 2008)
The influence of an alkali earth (Ba/Sr) element in small quantities (< 1 at.%) on non-linear electrical properties of 98.5% SnO2 + 1% CoO + 0.5% Ta2O5 (all in at.%) varistor system has been investigated. The non-linear coefficient increases from 33 to 52 whereas breakdown field strength varies 5025-6050 V cm(-1) for the barium-doped samples. In case of strontium-doped specimens moderate increase in non-linear coefficient but significant increase in breakdown field is observed. It is proposed that due to ionic size misfit, Ba and Sr segregates to grain boundaries thereby modifying their barrier properties. The contribution from grain boundary phase to the electrical property is confirmed by the impedance analysis. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Oxide materials; scanning electron microscopy; Sintering